2017
DOI: 10.4172/2329-8901.1000163
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lactobacillus and Bifidobacterium Combination on the Gut Microbiota, Clinical Course, and Local Gut Inflammation in Patients with Ulcerative Colitis: A Preliminary, Single-center, Open-label Study

Abstract: Background: Ulcerative colitis (UC) is one of the chronic, relapsing, inflammatory disorders of the gut and is characterized by inflammation limited in most cases to the colon. Since gut microbiota play a critical role in the development and perpetuation of intestinal inflammation, the addition of probiotics to this complex system may exert a positive influence on gut inflammatory reactions. Methods:A single center, open-label, intention-to-treat study involving patients with moderate-to-severe UC was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Xu et al demonstrated that some patients with COVID-19 presented microbial dysbiosis with decreased Lactobacillus and Bifidobacterium in fecal samples (Xu et al 2020). These bacteria play an important role in gut homeostasis and neurological function (Ni et al 2019), and supplementation with these bacteria can improve gut inflammation in ulcerative colitis patients (Pilarczyk Zurek et al 2017).…”
Section: The Microbiota Gut-lung Axis and Immune Response In Obesitymentioning
confidence: 99%
“…Xu et al demonstrated that some patients with COVID-19 presented microbial dysbiosis with decreased Lactobacillus and Bifidobacterium in fecal samples (Xu et al 2020). These bacteria play an important role in gut homeostasis and neurological function (Ni et al 2019), and supplementation with these bacteria can improve gut inflammation in ulcerative colitis patients (Pilarczyk Zurek et al 2017).…”
Section: The Microbiota Gut-lung Axis and Immune Response In Obesitymentioning
confidence: 99%
“…Chen et al [ 312 ] reported that the probiotic mixture of B. infantis , L. acidophilus , and Enterococcus faecalis with or without Bacillus cereus could restore the relative abundance of Lactobacillus , Bifidobacterium , Bacteroides , and Akkermansia in a mouse model of DSS-induced chronic colitis. In UC patients, a mixture of Lactobacillus and Bifidobacterium significantly increases the population of Proteobacteria and reduces Gramnegative rods [ 313 ].…”
Section: Gut Microbiota In Ibd Therapeuticsmentioning
confidence: 99%
“…In patients of UC, consumption of a mixture of Lactobacillus and Bifidobacteria reported a significant increase in the population of genera of Proteobacteria and reduction in Gram-negative rods. Supplementation of the probiotic mixture had a significant effect on the alteration of the gastrointestinal microbiome ( Pilarczyk-Żurek et al, 2017 ). Similarly, several other studies also reported that consumption of probiotics successfully restores and modulates a healthy microbial ecosystem as a treatment for IBD in patients ( Liu et al, 2020a , Liu et al, 2020b , Xia et al, 2020 ).…”
Section: Defining Pro- and Prebiotic Mechanisms In Ibdmentioning
confidence: 99%
“…Pathogenesis of IBD might be engendered by the rising of abnormal microflora in the gut. Oral administration of probiotics is widely practiced for various health improvements, including as therapies for gut-related disorders ( Altun et al, 2019 , Pilarczyk-Żurek et al, 2017 , van der Waal et al, 2019 ). Studies conducted to evaluate the efficiency of probiotics in the IBD, that demonstrated in animal models are summarized in Table 1 and the clinical intervention are summarized in Table 2 .…”
Section: Arising Probiotic Prebiotic and Synbiotic Therapy For Ibdmentioning
confidence: 99%
See 1 more Smart Citation